Strengthening interaction from direct to virtual basis: Insights from ethical and professional empowerment - Huda M.; Maseleno A.; Jasmi K.A.; Mustari I.; Basiron B. (Research India Publications, 2023)
The shift paradigm of interaction way from live basis to virtual one has been widely emerged around the world in the last decade. However, the challenging issues like immoral behaviour such as cyberbullying cannot be escaped across borderless space. The need to exposure the extent of empowerment ethics referring to personalised learning and internet plus should be taken into account in the way to solve in the wise basis. This paper attempts to examine the moral engagement in underlying the interaction basis in terms of human communities including the on commitment caring, friendship and trust. Literature review from reviewed journals and books was conducted in the view of keyword. The finding reveals strengthening interaction from the direct basis to digital one refers to possess engagement between professional and ethical engagement. This study is expected to contribute in providing innovative approach on moral based digital interaction with enhancing capacities and abilities to improve the learning capacity engaged in operating the technology tools appropriately and wisely. Research India Publications.